Effect of dexamethasone as an adjuvant with bupivacaine in transversus abdominis plane block for post-caesarean analgesia - Dhital, Aashish; Maharjan, Manju; Basnet, Ujjwal (Journal of Chitwan Medical College, 2026)
Introduction: Regional anaesthesia, like transversus abdominis plane (TAP) block, are valuable adjuncts to multimodal analgesia; however, their optimal pharmacological combinations remain under investigation. This study evaluated the efficacy of adding dexamethasone to bupivacaine in TAP block for caesarean delivery. Method: In this prospective, randomized, double-blind study, at Paropakar Maternity and Women’s Hospital, Nepal, from Nov 2024 to Apr 2025, after ethical approval, 52 elective caesarean sections under spinal anaesthesia received bilateral TAP block with either bupivacaine alone (Group B, n=26) or bupivacaine plus dexamethasone (Group BD, n=26). Postoperative pain scores (NRS 0-10) at 2, 4, 6, 8, 12 and 24 hours, duration of analgesia, total opioid consumption, and adverse effects were analysed. Statistical analysis was performed with IBM SPSS v.24, for mean±SD or median (IQR) as appropriate, Mann-Whitney U test for non-normally distributed data, and Fisher’s exact test for dichotomous outcome. Statistical significance was set at a two-tailed p-value <0.05. Result: Group BD showed a significantly longer duration of analgesia than Group B (median 9.6 h [IQR 8.0–11.5] vs. 6.7 h [5.4–8.0], p<0.001). Pain scores were lower in Group BD at 6 hours (median 3 [2–3] vs. 4 [3–5], p=0.007). Ketorolac use did not differ significantly (p=0.105). Rescue pethidine was required in 7(26.9%) in Group B versus 1(3.8%) in Group BD (p=0.049). Nausea/vomiting occurred in 10(38.5%) vs. 2(7.7%) patients, respectively. Conclusion: Adding dexamethasone to bupivacaine in TAP block significantly prolongs analgesia, reduces early postoperative pain and lowers opioid requirements in post-caesarean section patients.